Impact of nicotine/smoking, alcohol, and illicit substance use on outcomes and complications of burn patients requiring hospital admission: systematic review and meta-analysis. Issue 7 (November 2020) - Klifto, Kevin M.; Shetty, Pragna N.; Slavin, Benjamin R.; Gurno, Caresse F.; Seal, Stella M.; Asif, Mohammed; Hultman, C. Scott
Highlights: Intoxicants were associated with more operations, graft loss, hospital/ICU LOS, intubation, mortality, and wound infections. Nicotine/smoking was associated with increased rate of intubation and wound infections. Alcohol was associated with increased days on a ventilator, intubation, inhalation injury, ICU LOS, and mortality. Substances were associated with increased %TBSA, hospital/ICU LOS, intubation, inhalation injury, and wound infections. Abstract: Burn patients admitted to the hospital with concurrent intoxication are believed to be at an increased risk of poor outcomes and the development of complications, however data varies within the literature and remains controversial. This systematic review and meta-analysis compared outcomes and complications between nicotine/smoking, alcohol, and/or substance use in 26, 512 burn patients admitted to the hospital to 299, 543 burn patients admitted without these characteristics. The PubMed, EMBASE, Cochrane Library, and Web of Science databases were systematically and independently searched. PRISMA and Cochrane guidelines were strictly followed. Clinical characteristics, nicotine/smoking use, alcohol use, substance use, outcomes and complications were recorded. Seventeen of the 27 studies included in the study, were eligible for meta-analysis, with results from 39 of the possible 84 outcomes and complications. In conclusion, this systematic review and meta-analysis found that compared to non-nicotine/smoking, non-alcohol, non-substance use burn patients, patients using nicotine/smoking, alcohol, and/or substances were associated with more burn related operations, higher rates of graft loss/failure, longer hospital LOS (length of stay), higher rates of intubation, longer ICU (intensive care unit) LOS, increased mortality, and increased wound/local skin infections. Patients using nicotine/smoking were associated with higher rates of intubation and wound/local skin infections. Patients consuming alcohol were associated with more days on a ventilator, had higher rates of intubation, higher rates of inhalation injury, longer ICU LOS, and increased mortality. Patients taking substances were associated with higher %TBSA (percent total body surface area) of burns, longer hospital LOS, higher rates of intubation, higher rates of inhalation injury, longer ICU LOS, and increased wound/local skin infections.